ROBOTIC TELESCOPE BART - Jelinek, M.; Kubanek, P.; Nekola, M.; Topinka, M.; Strobl, J.; Hudec, B.; Castro-Tirado, A. J.; de Mateo Sanguino, J. (Одеські астрономічні публікації, 2017)
BART (Burst Alert Robotic Telescope) is a small remote controlled robotic CCD telescope, devoted to rapid observation of prompt gamma ray burst transients. During its operation since early 2001, it had three prompt observations With world-competitive response time. The constraints to object magnitude were estimated and published in GCN circulars. Telescope is located in Astronomical Institute of the Czech Academy of Sciences in Ondrejov. This poster describes its basic properties and its new control system, named RTSQ, Which is in service since February 2003.